Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0268121
|View full text |Cite
|
Sign up to set email alerts
|

Developing health and environmental warning messages about red meat: An online experiment

Abstract: Introduction The United States has among the highest per capita red meat consumption in the world. Reducing red meat consumption is crucial for minimizing the environmental impact of diets and improving health outcomes. Warning messages are effective for reducing purchases of products like sugary beverages but have not been developed for red meat. This study developed health and environmental warning messages about red meat and explored participants’ reactions to these messages. Methods A national convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Some studies have suggested that healthy dietary habits are more stable over time than unhealthy ones [3,40,41]; hence, parental feeding practices conducive to the development of healthy eating behaviors as a source of childhood food experiences as well as perceived nutrition concerns were included in the study as explanatory factors for changes in food intake in early adulthood and diet quality. Since a relationship between these variables was assumed, the following hypotheses were formulated: (1) Having childhood food experiences related to parents' monitoring practices and healthy eating guidance is associated with higher diet quality in early adulthood; (2) higher level of nutrition concerns is associated with higher diet quality in early adulthood; (3) having childhood food experiences related to parents' monitoring practices and healthy eating guidance is associated with more positive changes in food intake during university studies; and (4) higher level of nutrition concerns is associated with more positive changes in food intake during the studying period.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that healthy dietary habits are more stable over time than unhealthy ones [3,40,41]; hence, parental feeding practices conducive to the development of healthy eating behaviors as a source of childhood food experiences as well as perceived nutrition concerns were included in the study as explanatory factors for changes in food intake in early adulthood and diet quality. Since a relationship between these variables was assumed, the following hypotheses were formulated: (1) Having childhood food experiences related to parents' monitoring practices and healthy eating guidance is associated with higher diet quality in early adulthood; (2) higher level of nutrition concerns is associated with higher diet quality in early adulthood; (3) having childhood food experiences related to parents' monitoring practices and healthy eating guidance is associated with more positive changes in food intake during university studies; and (4) higher level of nutrition concerns is associated with more positive changes in food intake during the studying period.…”
Section: Introductionmentioning
confidence: 99%
“…This study used both health and environmental warnings in the labeling policy condition, so we were unable to disentangle the effects of the 2 types of warnings. Our previous research has found that health warnings and “combined” warnings that include both health and environmental messages are perceived as more effective than warnings that include only environmental messages [ 24 , 25 ] suggesting that the health warning may have been responsible for most of the observed reductions in red meat purchases in this study. In contrast, a study in the UK found that nutrition labels (Nutriscore) did not impact the healthfulness of purchases in an online experimental store but that environmentally focused “ecolabels,” either alone or in combination with nutrition labels, improved the sustainability of purchases [ 43 ].…”
Section: Discussionmentioning
confidence: 72%
“…The warning labels were designed based on previous research on warning efficacy [ 19 , 22 ] and nutrient warning labels in effect globally [ 23 ]. We tested several health and environmental warnings for red meat [ 24 , 25 ] and selected one for each topic (health and environment) based on perceived message effectiveness, evidence for the claims, literacy, and political feasibility through consultation with nutrition and environmental scientists and public health lawyers. The tax level of 30% was determined as a tax level likely to reduce health and environmental harms [ 8 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…For participants in the warning labels or combined warning labels + tax trial arms, the store displayed health and environmental warning labels next to foods containing red meat. The two labels were used simultaneously based on the results of previous research that found that presenting both health and environmental warning labels together may be more effective than presenting either alone [ 26 , 27 ]. For participants in the tax or combined warning labels + tax trial arms, the store displayed prices for foods containing red meat that were 30% higher than the control.…”
Section: Methodsmentioning
confidence: 99%